1991
DOI: 10.1083/jcb.112.2.345
|View full text |Cite
|
Sign up to set email alerts
|

Activation of LFA-1 through a Ca2(+)-dependent epitope stimulates lymphocyte adhesion.

Abstract: Abstract. The leukocyte function-associated molecule-1 (LFA-1) plays a key role in cell adhesion processes between cells of the immune system. We investigated the mechanism that may regulate LFA-1-1igand interactions, which result in cell-cell adhesion. To this end we employed an intriguing anti-LFA-1 ot mAb (NKI-L16), capable of inducing rather than inhibiting cell adhesion. Aggregation induced by NKI-L16 or Fab fragments thereof is not the result of signals transmitted through LFA-1. The antibody was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
104
1
2

Year Published

1992
1992
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 202 publications
(114 citation statements)
references
References 56 publications
7
104
1
2
Order By: Relevance
“…Nevertheless, a striking parallel exists between the earlier observations with NKI-L16 and those reported with TS2/16 in this paper ( The induction of VLAmediated cell adhesion by TS2/16 is dependent on metabolic energy, since a combination of deoxyglucose and sodium azide prevents induction of adhesion. We have previously reported that induction of LFA-l-mediated cell adhesion is not affected by sodium azide (Van Kooyk et al, 1991). Similarly deoxyglucose alone does not affect adhesion (our unpublished results).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Nevertheless, a striking parallel exists between the earlier observations with NKI-L16 and those reported with TS2/16 in this paper ( The induction of VLAmediated cell adhesion by TS2/16 is dependent on metabolic energy, since a combination of deoxyglucose and sodium azide prevents induction of adhesion. We have previously reported that induction of LFA-l-mediated cell adhesion is not affected by sodium azide (Van Kooyk et al, 1991). Similarly deoxyglucose alone does not affect adhesion (our unpublished results).…”
Section: Discussionmentioning
confidence: 87%
“…The antibody induces homotypic lymphocyte aggregation, as well as binding to purified ICAM-1 (Van Kooyk et al, 1991). In addition, the antibody enhances LFA-l-dependent adhesion to endothelium (our unpublished results).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition to the amount of expression of cell surface adhesion molecules, the functional state of integrins can be regulated, leading to changes in the affinity for counterligand binding without affecting the level of cell surface expression [11]. Changes in T cell integrin activity can be induced in vitro by a variety of stimulating agents, such as phorbol esters, calcium ionophore, and cross-linking of T cell receptors like CD2, CD3, CD7, and CD28 [3,[12][13][14]. Furthermore, the activation state of integrins can be altered by antibodies against ␤ 1 integrins, like 8A2, that bind to the receptor and induce a more active form [15] or by alterations of the extracellular cation milieu, both of which appear to affect the conformation of the integrin binding site [16,17].…”
Section: Introductionmentioning
confidence: 99%